Pengetahuan Lokal Tumbuhan Obat Oleh Pengobat Tradisional di Desa Antan Rayan Kabupaten Landak Kalimantan Barat - Marlina Pakpahan; Yeni Mariani; Yanieta Arbiastutie; Fathul Yusro (Fakultas Teknik, 2022)
Traditional healers (shamans or Batra) are people who have local knowledge in concocting plants as medicine to treat diseases suffered by the community. Currently, the number of those who are still practicing traditional medicine is decreasing. The purpose of this study was to document the local knowledge possessed by traditional healers or shamans in Antan Rayan Village, Landak Regency, West Kalimantan. The selection of respondents (traditional healers) was carried out using the snowball method. Respondents were interviewed regarding their local knowledge about the plants used to treat diseases in the Antan Rayan village community, the parts of the plants used, processing and usage methods, and the frequency of use. In Antan Rayan's village, four traditional healers (shaman/battra) still carry out traditional medicine using medicinal plants. From this study, 86 medicinal plant species were documented and included in 31 families, and Lamiaceae was the most commonly used family. These healers use these plants to treat various diseases the villagers suffered. The leaf is the most widely used part of the plant (44%). The most commonly used processing and usage method is boiling (48% and 54%), with the most common frequency being three times a day (45%).